(untitled) - Draper, C. G. (White Plains, NY, 2002)
Introduce your students to the works of famous American authors, while helping them build their reading, vocabulary, writing, and discussion skills.
Keywords: Reading comprehension,Đọc hiểu,Truyện ngắn, Mỹ,Short stories, American; Câu hỏi và bài tập,Thích ứng,Adaptations